Knowledge and Attitudes towards behavior of HIV/AIDS Patients Management among Dental Students: Observational Study (Universitas Muhammadiyah Yogyakarta, 2023)
In 1981, AIDS was first recognized in the United States. Every year, AIDS cases always increase. The incidence of cross-infection cases in dentists reaches 36% when managing HIV/AIDS patients. Having good knowledge and attitudes can lead to good behavior towards the management of HIV/AIDS patients. The formation of knowledge, attitudes, and good behavior will increase over time, along with the experience of a dentist. This research aims to determine the relationship between the knowledge and attitudes of dental students at RSGM UMY and the management behavior of HIV/AIDS patients. This research is an analytical observation with a cross-sectional approach that used a questionnaire instrument. The respondents of this research were 75 dental students. This research questionnaire includes knowledge, attitudes, and behavior about HIV/AIDS towards the management of HIV/AIDS patients. Data analysis used Chi-square analysis. The results of the descriptive analysis showed that 93.3% of dental students had high knowledge and positive attitudes, and 6.7% had moderate knowledge and were neutral towards HIV/AIDS patients. 77.3% of dental students fell into the good behavior category, 12% in the moderate behavior category, and 10.7% in the bad behavior category. The results of statistical tests using Chi-square obtained p value = 0.456 ( 0.05), indicating no significant relationship between research variables. Based on the results of the research, there was no significant relationship between the knowledge, behavior, and attitudes of dental students at RSGM UMY and the management behavior of HIV/AIDS patients.